Reduction of sea turtle population recruitment caused by nightlight: Evidence from the Mediterranean region. (1st March 2018) - Dimitriadis, Charalampos; Fournari – Konstantinidou, Ivoni; Sourbès, Laurent; Koutsoubas, Drosos; Mazaris, Antonios D.
Abstract: The spread of artificial night lighting is increasingly acknowledged as a major threat to global biodiversity. Identifying and exploring the impacts of nightlight pollution upon species behavior, ecology and population dynamics could enhance conservation capacity. Sea turtle hatchlings emerge from nest at night and use visual cues to direct towards the brightest and lowest horizon, eventually leading them to the sea. Nightlight pollution could alter the cues perceived, disorienting the fragile hatchlings. We examined the level of artificial lighting and orientation patterns of sea turtles hatchling, in Zakynthos Island, Greece, one of the main nesting rookeries of the loggerheads ( Caretta caretta ) in the Mediterranean Sea. We analyzed movement patterns of 5967 hatchlings from 230 nests, and demonstrate that nightlight pollution could reduce population recruitment by more than 7%, suggesting that mitigation measures should become a high conservation priority. Our results further suggest that the responses of sea turtle hatchlings to artificial nighttime lighting could vary significantly depending on various factors, either anthropogenic or natural. Local conditions operating at the nesting site level determine the fine scale responses of hatchlings, thus conservation measures should be drawn in respect to site-specific properties. Graphical abstract: Highlights: Sea turtle hatchlings response to night lights is reported in the Mediterranean. Significant impact of artificial night lights upon hatchlings orientation patterns. Nightlight pollution can reduce population recruitment by more than 7%. Conservation measures should be drawn in respect to site-specific properties.